2017
DOI: 10.47125/jesam/2017_sp1/03
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Emission Inventory of a Commercial-Scale Jatropha (Jatropha curcas L.) Biodiesel Processing Plant

Abstract: Biofuel feedstock development is in limelight because of its pronounced capability to reduce greenhouse gas emissions (GHG). The move towards renewable energy intensified researches to provide concrete attestations that could be benefited from the effort. This research assessed the GHG reduction potential of biodiesel produced from Jatropha curcas L., relative to that of the conventional petroleum diesel. Computations were based on a standard 30-MLPY biodiese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…• Jatropha trees have been grown for 3-4 years and the seeds yields are relatively stable [64]. The age of Jatropha trees is assumed, because only when the trees are 3 years old, they will give stable fruits production [65]. • In order to reduce transportation costs, the oil extraction equipment is nearby (within 2 km) the biodiesel production plant.…”
Section: Functional Unit and Assumptionsmentioning
confidence: 99%
“…• Jatropha trees have been grown for 3-4 years and the seeds yields are relatively stable [64]. The age of Jatropha trees is assumed, because only when the trees are 3 years old, they will give stable fruits production [65]. • In order to reduce transportation costs, the oil extraction equipment is nearby (within 2 km) the biodiesel production plant.…”
Section: Functional Unit and Assumptionsmentioning
confidence: 99%
“…The nonrenewable energy consumption (NRE) and greenhouse gas (GHG) emissions reduction were in the range of 6.9-21.7% and 24.7-42.6% compared to conventional diesel. Obligado et al, (2017) [17] studied the GHG reduction potential of biodiesel produced from Jatropha, relative to that of the conventional diesel. The results indicated that that the global warming potential of the Jatropha biodiesel is lower 24.2% than that of conventional diesel because savings acquired from utilizing the byproducts to produce electricity.…”
Section: Introductionmentioning
confidence: 99%
“…The non-renewable energy consumption (NRE) and greenhouse gas (GHG) emission reduction were in the range of 6.9-21.7% and 24.7-42.6% compared to conventional diesel. Obligado et al (2017) [17] studied the GHG reduction potential of biodiesel produced from Jatropha, relative to that of the conventional diesel. The results indicated that the global warming potential of the Jatropha biodiesel is 24.2% lower than that of conventional diesel because of the savings acquired by utilizing the byproducts to produce electricity.…”
Section: Introductionmentioning
confidence: 99%